Experimental ulcerative herpetic keratitis. I. Systemic immune responses and resistance to corneal infection. Issue 2 (February 1981) - Carter, C; Easty, D L
Abstract : The influence of previous infection with herpes simplex virus (HSV) on the susceptibility of rabbits to corneal inoculation of the virus was studied by means of the microtitration model for ulcerative herpetic keratitis. Systemic immune responses were assayed after skin and eye infections by means of the lymphocyte transformation (LT) and complement fixation (CF) tests. Both cutaneous and ocular primary infections resulted in cellular and humoral immune responses to HSV. In comparison to primary ocular infection, corneal disease in rabbits with previous skin infection ('secondary corneal infection') resulted in earlier initiation of cellular and humoral immune responses, while complement-fixing antibody titres reached a higher level. A previous cutaneous infection ('immunisation') provided considerable protection to the cornea and also accelerated recovery from corneal ulcerative disease. A correlation was observed between the initiation of the lymphocyte transformation response and the beginning of healing of corneal ulceration. A previous unilateral ocular infection induced an even higher degree of corneal resistance in that eye, and the opposite eye was protected to the same extent as by cutaneous immunisation.